2016
DOI: 10.1007/s00442-016-3788-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal survival estimation for a long-distance migratory bird and the influence of winter precipitation

Abstract: Conservation of migratory animals requires information about seasonal survival rates. Identifying factors that limit populations, and the portions of the annual cycle in which they occur, are critical for recognizing and reducing potential threats. However, such data are lacking for virtually all migratory taxa. We investigated patterns and environmental correlates of annual, oversummer, overwinter, and migratory survival for adult male Kirtland's warblers (Setophaga kirtlandii), an endangered, long-distance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 77 publications
4
101
1
Order By: Relevance
“…Although wintering grounds have strong carry-over effects on breeding success (Bearhop et al 2004, Latta et al 2016, Rockwell et al 2017, and Sacred Kingfisher individuals are known to be faithful to the same wintering site (Woodall & Kirwan 2018b), the ability of the Sacred Kingfisher to adapt to its wintering grounds will be limited by the constraints placed upon the population by the demands of its breeding grounds and its migration route. The Sacred Kingfisher is found in mangrove habitat throughout the region, regardless of island size (but with the addition of the Collared Kingfisher as a potential competitor on smaller islands).…”
Section: Our Results Demonstrated a Clear Split In Collaredmentioning
confidence: 99%
“…Although wintering grounds have strong carry-over effects on breeding success (Bearhop et al 2004, Latta et al 2016, Rockwell et al 2017, and Sacred Kingfisher individuals are known to be faithful to the same wintering site (Woodall & Kirwan 2018b), the ability of the Sacred Kingfisher to adapt to its wintering grounds will be limited by the constraints placed upon the population by the demands of its breeding grounds and its migration route. The Sacred Kingfisher is found in mangrove habitat throughout the region, regardless of island size (but with the addition of the Collared Kingfisher as a potential competitor on smaller islands).…”
Section: Our Results Demonstrated a Clear Split In Collaredmentioning
confidence: 99%
“…The sensitivity of the KIWA's population to winter droughts was evident from projection modeling, which indicated that a decrease in Bahamas March rainfall >12.4% from current mean levels could cause the size of the KIWA population to decrease due to winter droughts alone [62]. Further contributing to concerns about rainfall effects on KIWAs and other migrant birds in the Caribbean are predictions of increased occurrence of droughts under multiple climate change scenarios in the Caribbean [63].…”
Section: Discussionmentioning
confidence: 99%
“…We now recognize that the abundance and distribution of migrant birds are limited by events occurring throughout the annual cycle [16,81] and that events happening in one stage may carry over to influence other stages [20,24,62,70]. Without knowledge of the relative importance of various limiting factors during breeding, migratory, and wintering periods on population dynamics for each species of conservation concern, it will be impossible to implement effective management actions for each of these migrant species [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations